Novel Topical Treatment for Dandruff & Dry Scalp Through Sustained Balance in Skin Microbiome - Xiao A; Warren C; Samady W; Bilaver L (Dove Medical Press, 2021)
Alexander Xiao, Christopher Warren, Waheeda Samady, Lucy Bilaver Northwestern University Feinberg School of Medicine, Center for Food Allergy and Asthma Research, Chicago, IL, USACorrespondence: Alexander Xiao Email Alexander.xiao@northwestern.edu